If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 2(X + -9) Reorder the terms: Y = 2(-9 + X) Y = (-9 * 2 + X * 2) Y = (-18 + 2X) Solving Y = -18 + 2X Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = -18 + 2X
| 3/4y-1/2=5/8y+1 | | 2(5x-1)=-82 | | -8(-4x-5)=-88 | | 2x+3=6+2x | | -7(8x+3)=-133 | | 4m+7=34 | | 240+.25m=412.50 | | p=100+-4Q | | 2x-14+5=-6+11 | | 15=10y-4y-3 | | 2(-7b+1)=-35 | | 9(3x-1)=4x-6x | | 2(7x-2)+3=-99 | | 2(4-2x)=-x+1 | | c^2+8cy+15y^2= | | x^4+2x^2+47=0 | | 3y+y=164 | | X^2-X=4X | | x^4+x^2+47=0 | | 4b^2+14b+60=0 | | 6+5x-8x=15 | | 8(z-9)=-22 | | y=-40+6x | | 13=-13b+5b | | v^2+14v+60=0 | | 7x-5=47.5 | | -3z+7z=-3z-3-z | | 3×4/5 | | 18-4y=3y+17 | | 8-b=5(b+4) | | -60x+32=32x+-60 | | -60x+32=-60x+60 |